A group I WRKY transcription factor regulates mulberry mosaic dwarf‐associated virus‐triggered cell death in Nicotiana benthamiana. (5th November 2021) - Sun, Shaoshuang; Ren, Yanxiang; Wang, Dongxue; Farooq, Tahir; He, Zifu; Zhang, Chao; Li, Shifang; Yang, Xiuling; Zhou, Xueping
Abstract: Geminiviruses constitute the largest group of known plant viruses and cause devastating losses to a wide range of crops and woody plants globally. Mulberry mosaic dwarf‐associated virus (MMDaV), identified from Chinese mulberry trees via small RNA‐based deep sequencing, is a divergent monopartite geminivirus belonging to the genus Mulcrilevirus of the family Geminiviridae . Previous studies have shown that plants employ multiple layers of defence to protect themselves from geminivirus infection. The interplay between plant and MMDaV is nevertheless less studied. This study presents evidence that MMDaV triggers hypersensitive response (HR)‐mediated antiviral defence in Nicotiana benthamiana plants. We show that the RepA protein of MMDaV is engaged in HR‐type cell death induction. We find that the RepA mutants with compromised nuclear localization ability impair their capabilities of cell death induction. Virus‐induced gene silencing of the key components of the R protein‐mediated signalling pathway reveals that down‐regulation of the nucleus‐targeting NbWRKY1 alleviates the cell death induction activity of RepA. We further demonstrate that RepA up‐regulates the transcript level of NbWRKY1. Furthermore, expression of RepA in N. benthamiana confers plant resistance against two begomoviruses. We propose that plant resistance against RepA can be potentially used to improve plant defence against geminiviruses in crops. Abstract : A group I WRKY transcription factor is up‐regulated by mulberry mosaic dwarf‐associated virus (MMDaV) and modulates MMDaV‐triggered cell death in Nicotinana benthamiana .